The Role of Heat Shock Proteins in Systemic Vascular Catastrophes and in Acute Vascular Diseases of an Eye - L. K. Moshetova; S. A. Usharova; S. V. Simonova; K. I. Turkina; I. N. Saburina (Oftalʹmologiâ)
The disruption of blood flow through the retinal vessels is undoubtedly a stressful situation for the body. In response to any stress, the body produces heat shock proteins or so-called stress proteins. Moreover, a number of modern studies indicate that HSP may act as autoantigens, which are components of the immune system involved in the pathogenesis of vascular pathologies. By now, a number of certain heat shock proteins (HSP 60, 70) have already been proven to play a significant role in the pathogenesis of atherosclerosis as well as various circulatory disorders in the cerebral vessels. In addition, the possibility of using the data on the content and concentration of certain HSPs and antibodies to them in the blood plasma of patients as diagnostic and prognostic markers of systemic vascular diseases is considered. On the visual organ side, HSPs have been found to have damaging effects on retinal ganglion cells and, together with antibodies produced in response to their presence, are involved in the pathogenesis of glaucoma. However, there is currently no data on the role of HSP in the pathogenesis of retinal blood flow disorders and the possibility of using these molecules as diagnostic or prognostic markers of such conditions.